A Set of Linear Equations to Calculate the Steady-State Operation of an Electrical Distribution System - Franco, John F. [UNESP]; Rider, Marcos J. [UNESP]; Lavorato, Marina [UNESP]; Romero, Ruben [UNESP]; Gualteros, M. V.; Rodriguez, PYA; Aldana, A. (Ieee, 2011)
In this paper, the calculation of the steady-state operation of a radial/meshed electrical distribution system (EDS) through solving a system of linear equations (non-iterative load flow) is presented. The constant power type demand of the EDS is modeled through linear approximations in terms of real and imaginary parts of the voltage taking into account the typical operating conditions of the EDS's. To illustrate the use of the proposed set of linear equations, a linear model for the optimal power flow with distributed generator is presented. Results using some test and real systems show the excellent performance of the proposed methodology when is compared with conventional methods.
Keywords: linear power flow; radial/meshed electrical distribution system; steady-state operation; distributed generation